Does a mature AIDS epidemic threaten growth? - José Cuesta (Inter-American Development Bank, Research Department, 2008)
This paper models the impact on economic growth of HIV/AIDS when the epidemic is in a mature phase, in contrast with previous studies focused on periods of expansion, as in African countries. Simulations for Honduras, the epicenter of the epidemic in Central America, show that AIDS is not likely to threaten economic growth through either labor or capital accumulation channels; impacts are estimated between 0.007 and 0.27 percent points of GDP growth annually for the period 2001-10. Likewise, increasing spending on prevention, public treatment subsidies and treatment access will not jeopardize economic growth prospects. Critical factors that slash economic growth in Africa (such as human capital reductions and shifts in relative skills) are not strong in Honduras.
Keywords: O4; J1; I1; 330; HIV/AIDS; Growth Models; Policy Simulations; Prevention; Honduras; AIDS; Wirtschaftswachstum; Honduras